THE CONCEPT OF «SHANARAQ» IN THE KARAKALPAK LANGUAGE (TAMADDUN NURI JURNALI, 2025)
This article examines the concept of shanarak in the culture of the Karakalpak people, its significance within national values, spiritual life, and its usage in literary works. Additionally, the study analyzes the semantic nuances and various meanings of the term shanarak. The article is of great importance for the study and development of the modern Karakalpak literary language, as well as for research into terminology related to traditional dwellings.